REVOLUTIONIZING DENTAL CARE: THE INFLUENCE OF RADIOLOGICAL TECHNOLOGY ON DENTAL ASSISTANTS AND NURSES' WORK - Alenezi, Noor Falah; Aldidab, Hanady Farhan; Alruwaili, Haya Knaider (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
This article, titled "Revolutionizing Dental Care: The Influence of Radiological Technology on Dental Assistants and Nurses' Work," delves into the transformative impact of advanced radiological technology in dental care, particularly focusing on the changing roles and responsibilities of dental assistants and nurses. It examines the historical evolution of radiological tools in dentistry, from their initial introduction to the integration of modern, sophisticated imaging techniques. The paper highlights how these technological advancements have necessitated new skill sets, specialized training, and adaptability among dental professionals. It explores the effects of these changes on workflow efficiency, patient care, and the overall dynamics within dental practices. Additionally, the article addresses the ethical, legal, and safety considerations that arise with the use of radiological technology in dental settings, emphasizing the importance of balancing innovation with patient welfare and privacy. The future trends in dental radiology and their potential implications for dental staff are also discussed, offering insights into the ongoing evolution of dental care practices. This comprehensive analysis aims to provide a thorough understanding of the integral role of radiological technology in shaping the work environment and responsibilities of dental assistants and nurses.